2021
DOI: 10.1136/gutjnl-2020-323800
|View full text |Cite
|
Sign up to set email alerts
|

Liver function test abnormalities at hospital admission are associated with severe course of SARS-CoV-2 infection: a prospective cohort study

Abstract: ObjectiveLiver injury has frequently been reported in COVID-19 patients. The clinical relevance of liver injury related to SARS-CoV-2 infection remains unclear with a need for prospective studies on the impact of liver function test (LFT) abnormalities at baseline.DesignData of 217 patients without pre-existing liver disease prospectively included in the COVID-19 registry of the LMU university hospital were analysed in order to assess the association of abnormal LFT at admission and course of the disease. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 52 publications
6
79
2
1
Order By: Relevance
“…A review of 310 patients admitted with COVID-19 to our institution in Dublin revealed abnormal liver blood tests were present in almost 50% of patients, in particular raised gamma-glutamyl transferase (gGT) levels (table 1), similar to that noted by Weber and colleagues. 1 In our patient cohort, hypoalbuminaemia on admission to hospital was also an independent predictor of mortality, validating the findings of their prospective study. Multivariate analysis of our cohort showed a significant association between COVID-19-related mortality and serum albumin on admission (OR 0.90, 0.85-0.96; p=0.002); in a model incorporating older age, male sex, high MULBSTA score (a predictive score of viral pneumonia mortality 4 ) and body mass index, hypoalbuminaemia predicted death, with area under the curve receiver operating characteristic at 0.8 (figure 1).…”
Section: Liver Injury Hypoalbuminaemia and Severe Sars-cov-2 Infectionsupporting
confidence: 86%
See 1 more Smart Citation
“…A review of 310 patients admitted with COVID-19 to our institution in Dublin revealed abnormal liver blood tests were present in almost 50% of patients, in particular raised gamma-glutamyl transferase (gGT) levels (table 1), similar to that noted by Weber and colleagues. 1 In our patient cohort, hypoalbuminaemia on admission to hospital was also an independent predictor of mortality, validating the findings of their prospective study. Multivariate analysis of our cohort showed a significant association between COVID-19-related mortality and serum albumin on admission (OR 0.90, 0.85-0.96; p=0.002); in a model incorporating older age, male sex, high MULBSTA score (a predictive score of viral pneumonia mortality 4 ) and body mass index, hypoalbuminaemia predicted death, with area under the curve receiver operating characteristic at 0.8 (figure 1).…”
Section: Liver Injury Hypoalbuminaemia and Severe Sars-cov-2 Infectionsupporting
confidence: 86%
“…We have read with interest the recent study published in Gut by Weber et al 1 outlining liver abnormalities in 217 patients admitted with COVID-19 infection in Germany. Along with respiratory failure, deranged liver blood tests have been demonstrated in many cohort studies of patients admitted with SARS-CoV-2 infection, the clinical relevance of which has been unclear to date.…”
Section: Liver Injury Hypoalbuminaemia and Severe Sars-cov-2 Infectionmentioning
confidence: 99%
“…In our case series, the liver function (both transaminases and bilirubin levels) at presentation and during the course of the disease was unremarkable, even in the severe cases. This is in contrast with the literature on immunocompetent patients with COVID-19, in whom liver function test abnormalities are associated with a severe course of the SARS-CoV-2 infection [13]. In a meta-analysis, including 3428 patients from 20 retrospective studies, liver dysfunction was significantly higher in critically ill patients with unfavorable outcomes in COVID-19 [14,15], as could also be observed in other coronaviral diseases (SARS and MERS) [16][17][18].…”
Section: Liver Function Test Abnormalitiescontrasting
confidence: 66%
“…The prognostic significance of elevated liver enzymes in patients infected with SARS-CoV-2 is currently debated. Some reports have demonstrated that elevations of serum liver enzyme levels are associated with adverse outcomes, including shock, intensive care unit (ICU) admission and mechanical ventilation 43,65,[71][72][73][74] . However, these studies could be prone to bias if patients with severe disease received more intensive laboratory monitoring, increasing the likelihood of detecting liver injury.…”
Section: Prognostic Significance Of Elevated Liver Enzymes In Covid-19mentioning
confidence: 99%